Answer:
[tex]x = -\dfrac{5}{2}[/tex]
Step-by-step explanation:
To solve the equation [tex]4^{-x} = 32[/tex], let's use method 1 (Write exponents using the same base).
[tex] 4^{-x} = 32 [/tex]
Since [tex]32 = 2^5[/tex], we can rewrite [tex]32[/tex] as [tex]2^5[/tex]:
[tex] 4^{-x} = 2^5 [/tex]
Now, we notice that [tex]4 = 2^2[/tex], so we can rewrite [tex]4[/tex] as [tex]2^2[/tex]:
[tex] (2^2)^{-x} = 2^5 [/tex]
Now, apply the power of a power rule which states [tex](a^m)^n = a^{mn}[/tex]:
[tex] 2^{-2x} = 2^5 [/tex]
Now, since the bases are the same, we can equate the exponents:
[tex] -2x = 5 [/tex]
Now, solve for [tex]x[/tex]:
[tex] x = \dfrac{5}{-2} [/tex]
[tex] x = -\dfrac{5}{2} [/tex]
So, the solution to the equation is:
[tex]x = -\dfrac{5}{2}[/tex]